Molecular characterization of Mycobacterium bovis infection in cattle and buffalo in Amazon Region, Brazil - Carneiro, Paulo A.M. (2020)
The aim of this study was to characterize Mycobacterium bovis from cattle and buffalo tissue samples, from two Brazilian states, and to analyse their genetic diversity by spoligotyping. Tissue samples from tuberculosis suspect animals, 57 in Amazonas State (12 cattle and 45 buffaloes) and six from Pará State (5 cattle and one buffalo) from slaughterhouses under State Veterinary Inspection, were isolated in culture medium Stonebrink. The positive cultures were confirmed by PCR and analysed by the spoligotyping technique and the patterns (spoligotypes) were identified and compared at the Mycobacterium bovis Spoligotype Database (http://www.mbovis.org/). There was bacterial growth in 44 (69.8%) of the tissues of the 63 animals, of which PCR for region of differentiation 4 identified 35/44 (79.5%) as Mycobacterium bovis. Six different spoligotypes were identified among the 35 Mycobacterium bovis isolates, of which SB0295, SB1869, SB0121 and SB1800 had already been described in Brazil, and SB0822 and SB1608 had not been described. The most frequent spoligotype in this study (SB0822) had already been described in buffaloes in Colombia, a neighbouring country of Amazonas state. The other identified spoligotypes were also described in other South American countries, such as Argentina and Venezuela, and described in the Brazilian states of Rio Grande do Sul, Santa Catarina, São Paulo, Minas Gerais, Mato Grosso do Sul, Mato Grosso and Goiás, indicating an active movement of Mycobacterium bovis strains within Brazil.